A randomized education trial of spaced versus massed instruction to improve acquisition and retention of paediatric resuscitation skills in emergency medical service (EMS) providers. (August 2019) - Patocka, Catherine; Cheng, Adam; Sibbald, Matthew; Duff, Jonathan P.; Lai, Anita; Lee-Nobbee, Patricia; Levin, Helen; Varshney, Terry; Weber, Bryan; Bhanji, Farhan
Abstract: Aim: Resuscitation courses are typically taught in a massed format despite existing evidence suggesting skill decay as soon as 3 months after training. Our study explored the impact of spaced versus massed instruction on acquisition and long-term retention of provider paediatric resuscitation skills. Methods: Providers were randomized to receive a paediatric resuscitation course in either a spaced (four weekly sessions) or massed format (two sequential days). Infant and adult chest compressions [CC], bag mask ventilation [BMV], and intraosseous insertion [IO] performance was measured using global rating scales. Results: Forty-eight participants completed the study protocol. Skill performance improved from baseline in both groups immediately following training. 3-months post-training the infant and adult CC scores remained significantly improved from baseline testing in both the massed and spaced groups; however, the infant BMV and IO scores remained significantly improved from baseline testing in the spaced: BMV (pre, 1.8 ± 0.7 vs post-3-months, 2.2 ± 7; P = 0.005) IO (pre, 2.5 ± 1 vs post-3-months, 3.1 ± 0.5; P = 0.04) but not in the massed groups: BMV (pre, 1.6 ± 0.5 vs post-3-months, 1.8 ± 0.5; P = 0.98) IO (pre, 2.6 ± 1.1 vs post-3-months, 2.7 ± 0.2; P = 0.98). Conclusion: 3-month retention of CC skills are similar regardless of training format; however, retention of other resuscitation skills may be better when taught in a spaced format.